1975
DOI: 10.1111/j.1348-0421.1975.tb00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Cell Differentiation in Caulobacter crescentus

Abstract: The growth of a stalked bacterium, Caulobacter crescentus, has been synchronized easily and reproducibly by a new method. When this bacterium is grown to a late log phase in nutrient broth at 30 C with aeration, swarmer cells are accumulated in the culture to 80% of the whole cell population. When this culture is inoculated into fresh pre-warmed broth at twentyfold dilution, it immediately initiates synchronous cell growth. Simultaneously, synchronous cell differentiation is monitored by the susceptibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

1976
1976
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
1
2
0
1
Order By: Relevance
“…The CFU indicate that the numbers of wild-type and mutant cells are similar in stationary phase despite the difference in optical density. Previous experiments have indicated that the proportion of swarmer cells increases in late exponential phase (14). We confirmed these results by separating and quantitating swarmer cells from all other cell types using density centrifugation of culture aliquots from different stages of a growth curve in PYE.…”
Section: Resultssupporting
confidence: 71%
“…The CFU indicate that the numbers of wild-type and mutant cells are similar in stationary phase despite the difference in optical density. Previous experiments have indicated that the proportion of swarmer cells increases in late exponential phase (14). We confirmed these results by separating and quantitating swarmer cells from all other cell types using density centrifugation of culture aliquots from different stages of a growth curve in PYE.…”
Section: Resultssupporting
confidence: 71%
“…Exospore formation is induced by nutrient starvation in Rhodomicrobium vannielii (Whittenbury and Dow, 1977). Swarmer cell differentiation is inhibited in late exponential phase in Hyphomicrobium , R. vannielii (Morgan and Dow, 1985) and in C. crescentus (Iba et al ., 1975; Morgan and Dow, 1985; Janakiraman and Brun, 1997). Phosphate starvation dramatically induces stalk synthesis in C. crescentus (Schmidt and Stanier, 1966), and starvation for nitrogen can block the differentiation of swarmer cells (Chiaverotti et al ., 1981).…”
Section: Introductionmentioning
confidence: 99%
“…It has been anecdotally observed that C. crescentus cultures in late exponential phase can contain an unusually large proportion of swarmer cells. The proportion of swarmer cells has been seen to rise from 35 to 60% between optical densities of 0.9 and 0.97 (94,105). This phenomenon, affectionately called "swarmer burst," may be the result of nutrient depletion.…”
Section: Metabolic Input Into Developmentmentioning
confidence: 98%